Bundling telecommunications services : competitive strategies for converging markets - Krämer, Jan (Studies on eOrganisation and Market Engineering, 2009)
With the advent of digital convergence, incumbent telephone and cable companies have begun to offer their services, such as voice telephony, Internet and TV in so-called triple play packages. While carefully recognizing the technological, legal and economic framework of the fixed-line telecommunications industry, this book investigates whether bundling is indeed a profitable pricing strategy for the firms and if it can possibly facilitate the leverage of market power into neighboring markets.